2024
DOI: 10.1177/00368504241231659
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media with effusion in adults during the SARS-CoV-2 epidemic

Yu Zhang,
Feifei Yang,
Yanan He
et al.

Abstract: Objectives The purpose of this study was to investigate the fluctuations in the prevalence of individuals diagnosed with otitis media with effusion (OME) during the SARS-CoV-2 pandemic, while also evaluating the persistence of SARS-CoV-2 in middle ear effusion (MEE) and assessing the effectiveness of tympanocentesis as a treatment modality for OME in this specific period. Methods The total number of outpatients and patients diagnosed with OME in our department was recorded for January 2022 and January 2023. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Liang et al [ 23 ] proposed that administering steroids via intratympanic injection is an optimal approach for minimizing systemic adverse effects. Zhang et al [ 31 ] reported that tympanocentesis has a beneficial therapeutic effect for these patients, as it aids in the clearance of SARS-CoV-2 in the MEE. It is essential for the medical process to consider the treatment effectiveness and its environmental impact, particularly in the context of the COVID-19 pandemic [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al [ 23 ] proposed that administering steroids via intratympanic injection is an optimal approach for minimizing systemic adverse effects. Zhang et al [ 31 ] reported that tympanocentesis has a beneficial therapeutic effect for these patients, as it aids in the clearance of SARS-CoV-2 in the MEE. It is essential for the medical process to consider the treatment effectiveness and its environmental impact, particularly in the context of the COVID-19 pandemic [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, upper respiratory tract viral infections trigger an inflammatory reaction in the nasopharynx, which might ultimately result in eustachian tube blockage. Zhang et al [ 31 ] observed that all patients with OME caused by COVID-19 exhibited Eustachian tube dysfunction and considered it a fundamental basis and pathway for OME development. Second, the Omicron variation of SARS-CoV-2 generates a higher and more sustained viral load in the nasopharynx than the previously predominant Delta version [ 33 ].…”
Section: Discussionmentioning
confidence: 99%